Inovasi Smart Green House dalam Mendukung Green Economy dan Produktivitas Pembibitan di Kelompok Tani “Hortikultura Makmur Bersama” Rejosari Tulungagung - Aries Dwi Indriyanti; Ahmad Ajib Ridlwan; Yunus; Catur Surya Saputra; Aji Catur Prayogo; Rizdana Galih Pambudi (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
The Farmers Group "Horticulture Makmur Bersama" in Rejosari Village, Gondang District, Tulungagung Regency, is one of the leading actors in the horticultural agricultural sector that provides superior vegetable and fruit seeds. The problems faced by the Farmer Group "Makmur Bersama Horticulture" are difficulties in controlling pests and diseases, maintaining the growing environment, and limited resources. Based on the problems faced, the service team provides solutions to solve these problems with the Smart Green House innovation. The differentiator in this innovation is an irrigation device with a movable concept. The method used in this service activity consists of problem identification, needs analysis, design/development, manufacturing and testing, training, implementation, monitoring and evaluation. The results of this service showed that the production of plant seeds increased by an average of 36%. The use of Smart Green House can control pests more effectively and reduce the excessive use of pesticides. This bright greenhouse has temperature, air humidity, soil moisture, and light sensors integrated with IoT. Based on this service activity, the importance of technology integration in a sustainable agricultural sector in supporting the green economy can be concluded. Smart Green House can contribute to food security and empower farmers to manage their agriculture modernly.